2020
DOI: 10.1039/c9na00588a
|View full text |Cite
|
Sign up to set email alerts
|

High throughput study on magnetic ground states with Hubbard U corrections in transition metal dihalide monolayers

Abstract: We present a high throughput study of the magnetic ground states for 90 transition metal dihalide monolayers TMX2 using density functional theory based on a collection of Hubbard U values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 52 publications
3
18
0
Order By: Relevance
“…Bulk FeCl 2 shows ferromagnetic coupling in the intralayer while antiferromagnetic coupling in the interlayer according to neutron diffraction analysis . It is reported that the electronic properties of the FeCl 2 monolayer are sensitive to electronic correlation effects . To study the electronic correlation effect of this system, we investigated the magnetic properties with different effective on-site Coulomb interactions ( U eff ) for bulk FeCl 2 and the results are shown in Table S1.…”
Section: Calculation Details and Modelsmentioning
confidence: 99%
“…Bulk FeCl 2 shows ferromagnetic coupling in the intralayer while antiferromagnetic coupling in the interlayer according to neutron diffraction analysis . It is reported that the electronic properties of the FeCl 2 monolayer are sensitive to electronic correlation effects . To study the electronic correlation effect of this system, we investigated the magnetic properties with different effective on-site Coulomb interactions ( U eff ) for bulk FeCl 2 and the results are shown in Table S1.…”
Section: Calculation Details and Modelsmentioning
confidence: 99%
“…It has a hexagonal lattice with a 1T structural phase, where each La atom is bonded to six N atoms. The 1T structural phase has been not only realized in experiments, such as 1T-MoS2, 3 1T-TaS2, 35 and 1T-TiSe2, 36 but also widely applied for stable structural searches, such as transition-metal dihalides 37 and transition-metal dinitrides, 11 indicating its rationality. The optimized lattice constant, La-N bond length, and N-N distance along the z-direction are 4.05 Å, 2.47 Å, and 1.60 Å, respectively.…”
mentioning
confidence: 99%
“…Dipole corrections are included in all calculations. The results considering the effective Hubbard U (with a semiempirical value of U = 3 eV [51]) and the spin orbit coupling (SOC) are used for comparison, which are presented in Supplementary Materials [50]. Finally, the transport properties for a two-probe device systems are calculated using the Atomistix Toolkit (ATK) 2018 package based on the DFT-LCAO and the NEGF method [52][53][54][55].…”
Section: Methodsmentioning
confidence: 99%